Pneumoretroperitoneum and Perirenal Air Associated With Pneumothorax in an Extremely Low-Birth-Weight Infant - Belma Saygili Karagol; Dursun Turkbay; Ugur Dilmen (Elsevier, 2011)
Pneumothorax-associated pneumoretroperitoneum and perirenal air have rarely been reported in infants. We report a case of an extremely low-birth-weight infant who developed pneumoretroperitoneum and perirenal air associated with tension pneumothorax and deteriorated acutely despite prompt pleural water-seal vacuum drainage system insertion. Our aim in presenting this case report is to emphasize keeping in mind that there could be extrapleural air leaks, such as pneumoretroperitoneum in patients with pneumothorax.